Obra escrita y predicación de san Josemaría Escrivá de Balaguer / Saint Josemaría Escrivá’s Written Works and Preaching - José Luis Illanes (Studia et Documenta)
A compilation of all the writings of Saint Josemaria, both published and unpublished, including notes that have been kept from his oral preaching. The author follows a historical chronological outline, starting with his first unpublished writings and finishing with works published posthumously.